Tradisi Hawear Tantel Ohoi Weduar Fer Kecamatan Kei Besar Selatan Barat Kabupaten Maluku Tenggara - Tutubun, Juliana; Matitaputty, Jenny Koce; Hetharion, Bety D S. (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
The Hawear Tantel tradition is a sasi tradition that has been passed down from generation to generation as a means of protecting the eyes of the Tutubun house and the Ohoi Weduar Fer community. The problem in this research is that the Hawear Tantel tradition is a sasi tradition that has been passed down from generation to generation from the ancestors' tete as a means of protecting the eyes of the Tutubun house and the Ohoi Weduar Fer community. The problem in this research is how the tradition of Hawear Tantel is implemented. What are the meanings contained in the implementation of the Hawear Aunt tradition? What values are included in the implementation of the Hawear Aunt tradition? The research method used in this research is qualitative research. Data collection techniques are observation, interviews and documentation.